Changes in intentions, behavior, and reasons to receive COVID-19 vaccination December 2020–August 2023 - Yanhan Shen; Kate Penrose; McKaylee M. Robertson; Laura Puzniak; Kristen E. Allen; Avantika Srivastava; Sarah G. Kulkarni; Joann M. Zamparo; Frank R. Ernst; Christian Grov; John M. McLaughlin; Denis Nash (Vaccine: X, 2025)
Background: Staying up-to-date with COVID-19 vaccination reduces the risk of severe COVID-19 outcomes, yet U.S. uptake remains low. We described changes in intentions, behavior, and reasons for receiving COVID-19 vaccines among individuals who completed a primary series and assessed predictors of not receiving an updated vaccine (BA.4/5 bivalent). Methods: We analyzed data from the community-based CHASING COVID Cohort, a sociodemographically diverse sample of U.S. adults enrolled March–July 2020. The study included adults who completed a primary SARS-CoV-2 vaccine series and participated in at least one quarterly follow-up assessment during April–October 2023. Primary exposures were sociodemographic characteristics and COVID-19 history. Outcomes included intentions to receive a COVID-19 vaccine, vaccine uptake, and self-reported reasons for receiving or not receiving COVID-19 vaccine over time between December 2020 and August 2023. Results: Among 4411 eligible participants, 58 % intended to get vaccinated in December 2020 (before broad availability), and 86 % received the 2021–2022 vaccine (monovalent) between September 2021 and August 2022. However, willingness to receive a bivalent vaccine between October and December 2022 declined by ≥10 %. Among those who received the primary series and 2021–2022 vaccine, 56 % received the 2022–2023 vaccine. The prevailing reason for non-receipt from Fall 2022 to Summer 2023 was doubts about vaccine effectiveness. Logistic difficulties were predominantly reported in Winter 2022 and confusion about eligibility increased in Spring/Summer 2023. Lower bivalent vaccine uptake was observed among younger, female, non-White, less-educated, lower-income, uninsured individuals, and residents of the South or rural/suburban areas. Those with recent SARS-CoV-2 infection or previous long COVID were less likely to receive updated vaccines. Present comorbidities did not impact vaccines uptake. Conclusions: Findings highlighted a 3-year decline in willingness and receipt of COVID-19 vaccinations following their public introduction. Broad messaging and targeted outreach are needed to reinforce the protection up-to-date COVID-19 vaccination provides against severe illness and death.